HUBUNGAN KUALITAS LAYANAN TERHADAP KEPUASAN PASIEN PUSKESMAS SUKABUMI KOTA PROBOLINGGO - Novi Sri Sandyawati (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2017)
This research was conducted by survey, the primary data collection method obtained directly from the original source, This research was conducted at Probolinggo Municipal Health Service, with the title "Service Quality Relations Against Patient Satisfaction of Sukabumi Puskesmas of Probolinggo Municipality". The variables of this study are the characteristics of the wishes and expectations of customers or the public on the quality of service, characteristics aspects of service quality and organizational characteristics based on customer perceptions. From result of data analysis obtained respondent express high level of satisfaction to service of puskesmas P1 at attribute of Service Type (4,075). Affordable tariff (4,825). (4.8) and sanitary cleanliness of the puskesmas (4.05), while for the attributes stated have sufficient level of satisfaction such as checking flow (3,875), comfort of waiting room and examination room (3.85), program accuracy (3, 15), drug safety (3,175), ticket proof (3.95) and quick service (3,025). As for the other attributes hospitality puskesmas (2.9) and the number of medical officers (2.975)